2015
DOI: 10.1210/jc.2014-4454
|View full text |Cite
|
Sign up to set email alerts
|

Association between Inflammation and Biological Variation in Hemoglobin A1c in U.S. Nondiabetic Adults

Abstract: HGI reflects the effects of inflammation on HbA1c in a nondiabetic population of U.S. adults and may be a marker of risk associated with inflammation independent of FPG, race, and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 41 publications
8
64
2
2
Order By: Relevance
“…These observations sit coherently with interrelationships of glucose, glycation, AGE production, oxidative stress, and inflammation in the genesis of diabetes complications (23), enhanced by the evidenced link between adipose dysmetabolism, inflammation, and the shift in LAR as a key orchestrator of such dysmetabolism (24). Regarding inflammation, we only measured PAI-1, but others have shown a relationship of CRP with hemoglobin glycation index (HGI) (25) and, further, with carotid artery intimal thickness (26).…”
Section: Discussionsupporting
confidence: 71%
“…These observations sit coherently with interrelationships of glucose, glycation, AGE production, oxidative stress, and inflammation in the genesis of diabetes complications (23), enhanced by the evidenced link between adipose dysmetabolism, inflammation, and the shift in LAR as a key orchestrator of such dysmetabolism (24). Regarding inflammation, we only measured PAI-1, but others have shown a relationship of CRP with hemoglobin glycation index (HGI) (25) and, further, with carotid artery intimal thickness (26).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, chronic in ammation was recognized to be involved in the development of hypertension [37]. The National Health and Nutrition Examination Survey previously suggested that HGI was independently associated with in ammatory biomarkers including C-reactive protein (CRP), polymorphonuclear leukocytes, and monocytes [38]. Following 6 weeks of low-AGEs diet intervention in diabetics, the concentrations of in ammatory markers such as high-sensitivity C-reactive protein and TNFα were signi cantly reduced [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid panel readings provided fasting high-and low-density lipoprotein cholesterol and triglycerides. 28 Serum adiponectin concentrations 29 and percentage of HbA1c 30 (in National Glycohemoglobin Standardization Program units, using a high−performance liquid chromatography system) were collected after a minimum 8 hours of fasting. Left ventricle fraction to the nearest 5%, derived by a study cardiologist from a modified Quinones technique, served as a semiquantitative measurement of left ventricular systolic function.…”
Section: Methodsmentioning
confidence: 99%